2018
DOI: 10.1093/ehjqcco/qcy044
|View full text |Cite
|
Sign up to set email alerts
|

A novel geriatric assessment frailty score predicts 2-year mortality after transcatheter aortic valve implantation

Abstract: A novel 8-element GA frailty score identified gradations in survival in patients declined for open heart surgery. Patients with higher GA frailty scores had significantly higher two-year mortality after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 55 publications
1
36
0
1
Order By: Relevance
“…Specifically related to TAVR, previous studies have examined the value of determining frailty for risk stratification. For example, a study in 2018 showed that 11% patients of average age of 83 died 2 years after TAVR, and a geriatric assessment frailty score cut-off at ≥4 predicted 2-year mortality with a specificity of 80% 21 . Another study showed that 242 out of 544 TAVR patients were frail 1 year after the procedure based on frailty definition 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically related to TAVR, previous studies have examined the value of determining frailty for risk stratification. For example, a study in 2018 showed that 11% patients of average age of 83 died 2 years after TAVR, and a geriatric assessment frailty score cut-off at ≥4 predicted 2-year mortality with a specificity of 80% 21 . Another study showed that 242 out of 544 TAVR patients were frail 1 year after the procedure based on frailty definition 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The research team developed an 8-item frailty scale [ 14 ]. The total score is calculated by adding different domain scores: cognition (MMSE ≥ 27 = 0 points, MMSE 20–26 = 1 point, MMSE ≤ 19 = 2 points), instrumental activity of daily living (NEADL ≤ 43 = 1 point), nutrition (BMI < 20.5 = 1 point), modified SOF (low energy = 1 point, weight loss (reported, not measured weight loss; therefore, modified) = 1 point, chair stand, not able = 1 point) [ 15 ], Charlson Comorbidity Index (≥ 3 = 1 point) [ 16 ], and psychological factors (HADS ≥ 15 = 1 point) [ 17 ].…”
Section: Measurementsmentioning
confidence: 99%
“…This cut-off had a specificity of 80% and sensitivity of 60% at predicting 2-year mortality for this population. In a receiver operating curve, the area under the curve was 0.81 (95% confidence interval 0.71–0.90) [ 14 ].…”
Section: Measurementsmentioning
confidence: 99%
“…Trans-catheter aortic valve implantation (TAVI) has been a standard therapy for severe aortic valve stenosis (AS), especially in high surgical risk patients [ 1 4 ]. Frailty, lower active daily life (ADL), or malnutrition have been reported as major predictors of poor long-term outcomes after TAVI [ 5 9 ]. Moreover, symptomatic AS was associated with poor clinical outcomes [ 10 ], whereas asymptomatic AS was associated with favorable clinical outcomes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%